Міські самоврядні інституції Наддніпрянської України 1775–1917 рр. в імперській історіографії - Бондаренко, О. В.; Bondarenko, O. (ЦНТУ, 2023)
Історіографічний аналіз засвідчує, що за імперської доби дослідники зробили певний внесок у питання розуміння сутностей, явищ та фактів, які стосувалися історії міського самоврядування Наддніпрянської України 1775–1917 рр. Однак зауважимо, що міському самоврядуванню приділялося значно менше уваги, ніж земському. Пояснюється це тим, що соціально-економічний розвиток імперії визначався не містянами, а селянством, яке становило переважну більшість населення і через це дослідники розглядали земства як основний інститут, з яким пов’язували перспективи розвитку правової держави та громадянського суспільства. The historiographical analysis proves that during the imperial era, researchers made a certain contribution to the issue of understanding the essences, phenomena and facts that related to the history of the city self-government of Dnipro Ukraine 1775–1917. However, we note that much less attention was paid to city self-government than to zemstvo. This is explained by the fact that the socio-economic development of the empire was determined not by the townspeople, but by the peasantry, which made up the vast majority of the population, and because of this, researchers considered the zemstvos as the main institution with which the prospects for the development of the rule of law and civil society were linked.
City self-governing institutions of Dnieper Ukraine 1775–1917 in imperial historiography
Keywords: Наддніпрянська Україна; самоврядні інституції; історіографія; Transdnieper Ukraine; self-governing institutions; historiography